PELAKSANAAN PROGRAM PARENTING PENINGKATAN KAPASITAS ORANG TUA DALAM MENANAMKAN PERILAKU HIDUP SEHAT BAGI ANAK USIA DINI BERBASIS ALA RASUL - Awaliyah, Salma Aisyah Fazrulloh; Rukanda, Nandang (IKIP Siliwangi Bandung, 2025)
The background of this research is that child development requires a family that acts as a center for children, where interactions between children and other families can make a foundation for children's attitudes towards other people and the surrounding environment. This study aims to determine the implementation of the parenting program to increase the capacity of parents in instilling healthy lifestyle behaviors for early childhood based on Ala Rasul. This study uses a qualitative descriptive emethod, with the number of samples in the study being one manager, one teacher, and 6 representatives of parents. Data collection techniques through interviews and observation. Based on the results of the study, it was found that the implementation of parenting to increase the capacity of parents in instilling healthy living behavior for early childhood based on the Ala Rasul has been going well following the purpose of this activity, namely increasing the capacity of parents in instilling healthy living behaviors in children, parents of students. gain knowledge that can be used at home where parents are examples when children are at home.Keywords: Early Childhood, Parenting, Healthy Lifestyle Ala Rasul.